Dark matter [compact disc, unabridged] : a novel - Crouch, Blake (Books on Tape ; Penguin Random House Audio, 2016)
A mind-bending, relentlessly paced science-fiction thriller, in which an ordinary man is kidnapped, knocked unconscious--and awakens in a world inexplicably different from the reality he thought he knew.